Quantum Interaction : 8th International Conference, QI 2014, Filzbach, Switzerland, June 30 -- July 3, 2014. Revised Selected Papers - Atmanspacher, Harald; Bergomi, Claudia; Filk, Thomas; Kitto, Kirsty; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 8th International Conference on Quantum Interaction, QI 2014, held in Filzbach, Switzerland, in June/July 2014. The 19 papers together with 20 invited keynotes presented in this book were carefully selected from 22 submissions. Quantum Interaction has developed into an emerging interdisciplinary area of science combining research topics in fundamental issues, semantic and memory, decision making, games, politics, and social aspects, non-locality and entanglement.
Fundamental Physics and the Mind { Is there a connection? -- What is quantum? Unifying Its Micro-Physical and Structural Appearance -- Feedback loops: a fundamental ingredient of information processing -- Semantics and Memory -- Semantic Composition Inspired by Quantum Measurement Expansion-by-Analogy: A Vector Symbolic Approach to Semantic Search -- Subadditivity of Episodic Memory States: a Complementarity Approach. A Vector Field Approach To Lexical Semantics -- Decision Making -- Quantum(-like) formalization of common knowledge: Binmore-Brandenburger operator approach -- Quantum(-like) decision making: on validity of the Aumann theorem -- Modelling Attitudes to Climate Change { An Order Effect and a Test Between Alternatives -- Towards a Quantum Probability Theory of Similarity Judgements -- Positive operator-valued measures in quantum decision theory -- Games, Politics and Social Aspects -- Aesthetics as Incentive: Privacy in a Presence Culture -- A Quantum Formalization for Communication Coordination Problems -- Financial payo functions and potentials -- Quantum like modeling of the non-separability of voters' preferences in the U.S. political system -- Transparency in Public Life. A Quantum Cognition Perspective -- Games with Type Indeterminate Players { A Hilbert Space approach to uncertainty and strategic manipulation of preferences -- Non-Locality and Entanglement -- Temporal Non-Locality: Fact or Fiction? -- Intentional Quantum Dynamics: Entangling Choices and Goals -- Towards an Empirical Test of Realism in Cognition.
Keywords: Computer science; Artificial intelligence; Information storage and retrieva; Computation by Abstract Devices; Artificial Intelligence; Information Storage and Retrieval; Quantum Computing; Information Systems Applications (incl. Internet).